Fate of the η′ in the quark gluon plasma - Andrey Yu. Kotov (Physics Letters B, 2019)
In this paper we study the η′ in Nf=2+1+1 lattice QCD simulations at finite temperature. Results are obtained from the analysis of the gluonic defined topological charge density correlator after gradient flow. Our results indicate the growth of the η′ mass above the pseudocritical temperature, associated with the chiral symmetry restoration. In the vicinity of the pseudocritical temperature the results are consistent with a small dip in the η′ mass. The magnitude of the dip is compatible with the reduction of the η′ mass obtained by experimental analysis and suggests that η′ mass comes close to zero temperature non-anomalous contribution. Keywords: η′ meson, Chiral symmetry, Nonzero temperature, Lattice QCD, QCD topology, Quark gluon plasma